2017
DOI: 10.1371/journal.pntd.0005782
|View full text |Cite
|
Sign up to set email alerts
|

A putative ATP/GTP binding protein affects Leishmania mexicana growth in insect vectors and vertebrate hosts

Abstract: BackgroundLeishmania virulence factors responsible for the complicated epidemiology of the various leishmaniases remain mainly unidentified. This study is a characterization of a gene previously identified as upregulated in two of three overlapping datasets containing putative factors important for Leishmania’s ability to establish mammalian intracellular infection and to colonize the gut of an insect vector.Methodology/Principal findingsThe investigated gene encodes ATP/GTP binding motif-containing protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Our data demonstrated that the promastigotes of the LmDUSP1 KO strain divide statically significantly slower compared to their wild type or Cas9 counterparts ( Figure 3B). This was reminiscent of the situation previously documented for L. mexicana with ablated LmxM.30.2090, a gene encoding a putative ATP/GTPase ALD1 [31].…”
Section: Experimental Infection Of Lutzomyia Longipalpissupporting
confidence: 58%
“…Our data demonstrated that the promastigotes of the LmDUSP1 KO strain divide statically significantly slower compared to their wild type or Cas9 counterparts ( Figure 3B). This was reminiscent of the situation previously documented for L. mexicana with ablated LmxM.30.2090, a gene encoding a putative ATP/GTPase ALD1 [31].…”
Section: Experimental Infection Of Lutzomyia Longipalpissupporting
confidence: 58%
“…A comparative genomic study with an underlying assumption that at least some of the Leishmania virulence factors might have been gained at the Leishmania node led to the identification of more than 20 candidate genes, albeit mostly with unknown functions. A gene encoding a putative ATP/GTPase was experimentally proven to affect L. mexicana growth in vitro and its ability to achieve maximal levels of parasite load in vivo in both mice and insects [41].…”
Section: Genomic Diversitymentioning
confidence: 99%
“…Genes and proteins involved in differentiation or infection maintenance are putative virulence factors. Nowadays, they are identified mainly by using NGS-based approaches [ 8 , 9 ] and analyzed with the help of functional genomics methods [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%